DNA microarrays and gene expression - Baldi, Pierre (Cambridge University Press, 2002)
DNA microarrays are revolutionizing biology and medicine. They can provide a snapshot of the level of gene expression in a cell and are therefore a powerful tool with which to study biological phenomena at the molecular level. This inter-disciplinary introduction will be essential reading for researchers of all disciplines.